Environment - Cornelia Ohl; Bernd Hansjürgens (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Many environmental problems are large scale in terms of geographical units and long-term with regard to time. We therefore find a coincidence of different causes and impacts that qualify the interplay between humans and nature as highly uncertain ("transparency challenge"). In consequence we see a need for innovative analytical methods and modelling approaches to supplement the traditional monitoring-based approach in environmental policy. This should allow capturing different degrees of uncertainty which in general is out of power of any monitoring activity. Moreover, with regard to the design of monitoring approaches it requires collecting and connecting data from different fields of social activities in regard of a divergence of natural and social systems' boundaries. This requires the provision of sufficient, frequently huge data sets ("availability challenge") that need to fit with each other ("compatibility challenge"). Even if these challenges are met data processing remains a very complex and time-consuming task which should be supported by a user-friendly infrastructure. We here see a comparative advantage in using the GIS technology and a nested structure for data provision supporting the up and down scaling of information and the access of data from different perspectives ("connectivity challenge") - a polluters, a victims and a regulators point of view.
Keywords: 330; Coincidence of causes and impacts; transparency challenge; availability challenge; compatibility challenge; connectivity challenge; GIS technology; nested structure of data provision